Aumento da eficiência total de armazenadores de energia compostos por eletrolisadores, células a combustível e hidretos metálicos - Kuhn, Vinicius Nizolli (2018)
The growing global energy consumption, the search for reduction in carbon emissions and climate problems highlight the importance of investment in low environmental impact energy systems. In this sense, the Generation and Storage Systems of Electrical Energy based on Hydrogen (AEH2) are a promising alternative technology, besides being a clean energy source, and acting as a bridge between the different energy sectors (electricity, heat and fuel). However, the overall efficiency of an AEH2’s is too limited. Due to hydrogen’s properties, a considerable portion of power is drained by storage system and another important portion is converted into heat by the AEH2’s equipments. In this research, it is intended to increase the efficiency of an AEH2 through theoretical and experimental study of the use of heat of its components. The AEH2 of this research is composed of an alkaline electrolyzer, a metal hydrides hydrogen storage and a PEM fuel cell stack. An experimental plant was conceived with this type of equipment for data acquisition, testing and research. The internal structure of each part of the equipment was built and a detailed description of its operation was carried out. Also, it was developed the mathematical modeling and equating of the AEH2’s components based on the experimental plant equipment. The computational models were validated from experiments. The interconnection between the models made it possible to simulate the hydrogen charging and discharging cycles taking into account the use of heat of AEH2’s components. From the results of the simulations it was estimated the potentials of power generation and the impact of the heat recovery on the overall efficiency of the AEH2. In addition, a new method was developed to monitor the temperature distribution in fuel cell itself, which allows an improved control of its temperature and contributes to the increase of its efficiency.